2015
DOI: 10.1016/j.ijscr.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone deficiency after unilateral adrenalectomy for Conn’s syndrome: a case report and literature review

Abstract: HighlightsWe report a case of postoperative hypotension and hyperkalemia in a unilateral adrenalectomy for Conn’s syndrome.We highlight that there are factors that may make certain populations more at risk for developing this complication.Increasing awareness about this complication and its consequences highlights the needfor close monitoring in increased risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Postoperative hyperkalaemia during the first month after unilateral adrenalectomy had been reported to affect up to 16% of patients in previous studies. 7,9,[12][13][14]19,20 Factors including age, duration of hypertension, renal function and tumour size were reported to predict the development of postoperative hyperkalaemia. 8,12,13 However, preoperative use of MRA was not associated with the prevention of hyperkalaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative hyperkalaemia during the first month after unilateral adrenalectomy had been reported to affect up to 16% of patients in previous studies. 7,9,[12][13][14]19,20 Factors including age, duration of hypertension, renal function and tumour size were reported to predict the development of postoperative hyperkalaemia. 8,12,13 However, preoperative use of MRA was not associated with the prevention of hyperkalaemia.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of transient hypoaldosteronism requiring mineralcorticoid replacement after adrenalectomy has been reported in some aldosterone-producing adenoma (APA) patients (12). A recent study reported the occurrence of prolonged “zona glomerulosa insufficiency” after adrenalectomy in up to 5% of APA patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current guidelines of the Polish Society of Hypertension on the management of primary aldosteronism (PA) associated with aldosterone-producing adenoma, the treatment of choice is unilateral laparoscopic adrenalectomy [1]. The literature finds few reports on postoperative hypoaldosteronism requiring mineralocorticoid replacement [2][3][4][5][6]. Literature data indicate that some patients who undergo adrenalectomy for PA present postoperative hyperkalaemia associated with the inability of the remaining adrenal gland to compensatory aldosterone production [2,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Huang et al reported a case of 62-yearold man with severe hyperkalaemia after adrenalectomy -laboratory tests showed a high level of PRA and low level of aldosterone, normal levels of cortisol and ACTH suggesting hypoaldosteronism as the cause of hypokalaemia [3]. Similarly, in 2015, Yorke et al described a case of 66-year-old female operated for Conn's syndrome, with subsequent postoperative hyperkalaemia and hypotension, successfully treated with fludrocortisone [2].…”
Section: Discussionmentioning
confidence: 99%